Retrieval of HCFC-142b (CH3CClF2) from ground-based high-resolution infrared solar spectra: Atmospheric increase since 1989 and comparison with surface and satellite measurements. (January 2017) - Mahieu, Emmanuel; Lejeune, Bernard; Bovy, Benoît; Servais, Christian; Toon, Geoffrey C.; Bernath, Peter F.; Boone, Christopher D.; Walker, Kaley A.; Reimann, Stefan; Vollmer, Martin K.; O'Doherty, Simon
Abstract: We have developed an approach for retrieving HCFC-142b (CH3 CClF2 ) from ground-based high-resolution infrared solar spectra, using its ν7 band Q branch in the 900–906 cm −1 interval. Interferences by HNO3, CO2 and H2 O have to be accounted for. Application of this approach to observations recorded within the framework of long-term monitoring activities carried out at the northern mid-latitude, high-altitude Jungfraujoch station in Switzerland (46.5°N, 8.0°E, 3580 m above sea level) has provided a total column times series spanning the 1989 to mid-2015 time period. A fit to the HCFC-142b daily mean total column time series shows a statistically-significant long-term trend of (1.23±0.08×10 13 molec cm −2 ) per year from 2000 to 2010, at the 2-σ confidence level. This corresponds to a significant atmospheric accumulation of (0.94±0.06) ppt (1 ppt=1/10 12 ) per year for the mean tropospheric mixing ratio, at the 2− σ confidence level. Over the subsequent time period (2010–2014), we note a significant slowing down in the HCFC-142b buildup. Our ground-based FTIR (Fourier Transform Infrared) results are compared with relevant data sets derived from surface in situ measurements at the Mace Head and Jungfraujoch sites of the AGAGE (Advanced Global Atmospheric Gases Experiment) network and from occultation measurements by the ACE-FTS (Atmospheric Chemistry Experiment-Fourier Transform Spectrometer) instrument on-board the SCISAT satellite. Highlights: An approach for retrieving HCFC-142b from ground-based infrared spectra is presented. The HCFC-142b trend over 1989–2015 is characterized. A recent slowing-down in the HCFC-142b atmospheric increase is observed. Comparison with satellite and in situ surface measurements is included.